The credibility of Works of Luke (Gospel-Acts) in the context of the Hellenistic Historiography (De Rebus Antiquis, 2020)
This collaboration aims to assess the “historicity” of the New Testament texts, those that have traditionally been viewed as presenting a “wrapper” more reliable environment. This task can not be undertaken without a prior insight into the differences that its various texts present, without explaining the different environments in which each tradition was forged, nor the intention of the various genres which was resorted. The work of Luke, consisting in the sum of the third synoptic gospel and the so called Acts of the Apostles, shows the more clearly diachronic perception, from the birth of Jesus to the establishment of christianism in Rome, and accounts for nearly one third of the New Testament text, much more if we consider that for their understanding is necessary to check with the other Synoptic Gospels and the Pauline Letters. The perspective of this study is that of the historian, not of the exegesis, Luke’s work is analyzed as if it were a text from the Hellenistic tradition. A text which has to answer, therefore, to an understandable literary canons for his hypothetical readers, a text wrote in the years of maximum brilliance of the Roma Empire, probably to the end of the first century, in a vague cultural and geographical context but which has to take into account the Palestinians problems after de Jewish war of 67-70 and the background of the religious struggle and theological creativity that, necessary, had to characterize a new religion, still in a formation process, building up and perfecting his definitive signs of identity. In this sense we have to assess the personality of the author and his level of commitment to the religious group which aims to present a semblance; of course, it is necessary to reveal the aim of the text, mediated by the genre and his audience. We must insert the particular information that Luke-Acts provides in a background and, when it was possible, corroborate his information checking with other contemporary sources. From this process we will be able to conclude if the information offered is reliable or not, if it that level of precision is impossible we will at least be able to declare if it is believable or, for the contrary, is artificial.
Keywords: New Testament; historiography; literary genres; Hellenistic culture